In Prayer and Protest: Understanding the Moral World of the SaphaHors in the Santal Parganas (1871–1947). (January 2016) - Sarkar, Anamitra
Abstract: In 1871 a sect called the SaphaHors or clean men emerged in the Santal Parganas in the shadows of the repression of the Santal rebellion of 1855. In an ambience of disillusionment, they sought to redefine their identity through a code of morality. These were, however, not a written code but passed down orally through generations by numerous gurus around whom the brotherhoods were formed. Through a study of the SaphaHors we seek to understand the evolution and significance of the moral code; the nature of the anti-colonialism which lay inchoate in the moral code; the syncretistic practices that constituted the moral world thereby opening possibilities of questioning stereotypes like Hinduisation of the tribes. The complex interplay between culture, power and identity helps to explain the mysteries behind the unique survival of the little known sect from the Santal Parganas.